2013
DOI: 10.1097/wnr.0b013e3283644b66
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in dreaming during short propofol sedation for upper gastrointestinal endoscopy

Abstract: Previous reports suggest that sex differences may exist in dreaming under anesthesia, but their results were inconclusive. The current study explored sex differences in the incidence and content of dreams during short propofol sedation for upper gastrointestinal endoscopy and investigated whether sex differences or dream content affect patient satisfaction with sedation. A total of 200 patients (100 men and 100 women) undergoing upper gastrointestinal endoscopy participated in this study. Patients were intervi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…In research on 100 men and 100 women undergoing short propofol sedation for upper gastrointestinal endoscopy, Xu et al showed that men dream statistically more often than women. They also found out that men reported dreams that were more meaningful, familiar, vivid, and memorable, with a higher incidence of recall [12]. A study by Tezcan and colleagues on a smaller sample did not find a statistical difference, although men had a higher dreaming ratio [8], as observed in our study.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…In research on 100 men and 100 women undergoing short propofol sedation for upper gastrointestinal endoscopy, Xu et al showed that men dream statistically more often than women. They also found out that men reported dreams that were more meaningful, familiar, vivid, and memorable, with a higher incidence of recall [12]. A study by Tezcan and colleagues on a smaller sample did not find a statistical difference, although men had a higher dreaming ratio [8], as observed in our study.…”
Section: Discussionsupporting
confidence: 82%
“…Patients who had dreams were more satisfied with their care than those who did not [11]. A study carried out by Xu and colleagues showed an incidence of dreaming of 24% and a statistically higher incidence of dreams in men than in women [12], while Tezcan et al reported an incidence of dreaming of 42%, with no sex differences [8]. All studies agree that dreams under propofol anesthesia have positive emotional content in most cases.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, participant patients could have met and communicated about the study contents and this communication would have induced suggestion of dreaming in controls. This so called treatment diffusion effect has been described and avoided in the study of Gyulaházi before (Xu et al, 2013). Except a small difference in American Society of Anesthesiologists physical status, characteristics of patients were not different between the groups and there were no systematic differences in anesthesia and surgical procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the incidence of dreaming varies with factors such as age, sex, the anesthesia technique applied, drugs, the severity of anesthesia and the postoperative interview time, but the incidence has a wide range of 1−81%. 17 A study by Uting et al 18 reported that 7% of 500 patients had a bad dreaming experience and 2% remembered this experience. In our study, 10 (8%) patients had experienced dreams during previous operations, and these dreams did not have bad or unpleasant features.…”
Section: Discussionmentioning
confidence: 99%